Fenomena Kecenderungan Online Disinhibition pada Siswa Kelas XI di SMA Swasta Banuhampu - Azira; M. Arif (Lembaga Yasin AlSys, 2026)
The development of digital technology has transformed adolescents’ communication patterns and given rise to the phenomenon of online disinhibition, namely the tendency of individuals to behave more freely, boldly, and expressively in online interactions than in face-to-face interactions. This phenomenon has the potential to influence students’ social behavior, communication patterns, and interpersonal relationships. This study aims to identify the level of online disinhibition tendencies among Grade XI students at SMA Swasta Banuhampu and analyze the factors influencing them. The study employed a descriptive quantitative approach with a survey design involving 100 Grade XI students who were active social media users. Data were collected using a questionnaire as the primary instrument and were supported by structured interviews and participant observation conducted over four weeks. The questionnaire data were analyzed using descriptive statistics and subsequently compared with the interview and observation findings to obtain a more comprehensive understanding. The findings indicate that 70% of the students had a high level of online disinhibition, 20% were in the moderate category, and 10% were in the low category. The most dominant aspects included the courage to express opinions, the freedom to express emotions, and impulsive behavior when interacting through social media. Anonymity was the primary factor encouraging students to express their opinions more boldly, whereas impulsive behavior and the expression of negative emotions in online interactions had the potential to affect their social relationships in real life. These findings emphasize the importance of collaboration between schools and parents in strengthening digital literacy and ethics so that students can use social media responsibly and maintain a balance between online and offline interactions.